Biocompatibilidade de sistemas adesivos autocondicionantes experimentais livres de HEMA - Barbosa, Marília Oliveira (2011)
HEMA is a monomer widely used in the adhesive systems, although the biologic performance has been found as negative it has been tried to solve this problem by testing new monomers with lower citotoxic potential. We analyzed the biocompatibility of five experimental dimethacrylate monomers: Bis-EMA 10, Bis- EMA 30, PEG 400, PEG 400 UDMA, PEG 1000. First, it was made an in vitro test using 3T3 mouse fibroblast cell culture. So, the cytotoxic test was made using primers at 20% and 2%. The dilutions were maintained in contact with the cells for a period of 24h and after the survival these cells was verified photometrically using MTT assay. After it was performed cytotoxic test with the resin bonds as follows: hese monomers were polymerized and leaving in immersion in DMEM for 24h and later the eluate obtained was inserted on the 3T3 cell for 24h. The statistical analysis was performed by Kruskal wallis method, followed by a multiple-comparison Dunn´s test (p<0.05). Second, the degree of conversion of adhesive resin was also analyzed.The results showed that related to the primers in the concentration of 2% only PEG 1000 group had no statistical difference with the control group. In the concentration of 20% there was no difference among Bis-EMA 10, PEG 1000 and the control group. Concerning to eluates there were no difference among Bis-EMA 10, PEG 400 UDMA and the control group. All monomers showed a degree of conversion similar than HEMA. Other studies are necessary using different concentrations and different cell lines because these monomers are promising in the use of adhesive systems.